2013
DOI: 10.1093/bja/aes450
|View full text |Cite
|
Sign up to set email alerts
|

Topical lidocaine to suppress trigemino-cardiac reflex

Abstract: analysis of standard, restrictive and supplemental fluid administration in colorectal surgery. Br J Surg 2009; 96: 331-41 3 Varadhan KK, Lobo DN. A meta-analysis of randomised controlled trials of intravenous fluid therapy in major elective open abdominal surgery: getting the balance right.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…33 During the time of preparation around the trigeminal nerve, the patients' HR and MABP also decreased significantly. 46 Later, in 2013, Chigurupati et al 47 described another case of microvascular decompression and TCR that, like the initial cases of Schaller, 46 needed an extremely long time to return to normal after cessation of the stimulus. 46 MABP fell 57%, from a mean of 81 mmHg before manipulation to 35 mmHg during the procedure, and then returned to 84 mmHg after manipulation.…”
Section: Microvascular Trigeminal Decompression (The Jannetta Procedure)mentioning
confidence: 99%
“…33 During the time of preparation around the trigeminal nerve, the patients' HR and MABP also decreased significantly. 46 Later, in 2013, Chigurupati et al 47 described another case of microvascular decompression and TCR that, like the initial cases of Schaller, 46 needed an extremely long time to return to normal after cessation of the stimulus. 46 MABP fell 57%, from a mean of 81 mmHg before manipulation to 35 mmHg during the procedure, and then returned to 84 mmHg after manipulation.…”
Section: Microvascular Trigeminal Decompression (The Jannetta Procedure)mentioning
confidence: 99%
“…92 The cessation of stretching, manipulation, and/or stimulation forms the most important part of treatment. 92 The cessation of stretching, manipulation, and/or stimulation forms the most important part of treatment.…”
Section: Anesthetic Management Of the Tcrmentioning
confidence: 99%
“…The growing and increasingly detailed literature published since this rep ort 6,13,14,16,18,20,[24][25][26] has demonstrated that stimulation of any of the sensory nerve endings of the trigeminal nerve (transmitted via the ciliary, pterygopalatine, or otic ganglia) activates the afferent arm of the TCR by way of the Gasserian ganglion. The trigeminal nerve then bridges the peripheral afferent component of the TCR with the central afferent component: the superficial medullary dorsal horn and the sensory nucleus of the trigeminal nerve.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20] Similarly, the oculocardiac reflex is reported to occur in ~17% of patients undergoing surgery for strabismus. 21 During neurosurgical procedures, abrupt and sustained traction of structures innervated by the trigeminal nerve is more prone to elicit the TCR than smooth and gentle traction.…”
Section: Introductionmentioning
confidence: 99%